Mudanças climáticas e saúde: revisão sistemática da literatura sobre os efeitos da temperatura ambiente no sistema cardiovascular humano - Casas, André Luís Foroni (2015)
In recent decades, cold and heat waves were recorded in all continents. An important effect of the ambient temperature variation is to cause abnormalities in the blood vessels and homeostatic mechanisms in humans, affecting the cardiovascular system. The aim of this study was conduct a survey on the effects of ambient temperature on the human cardiovascular system through a systematic review. Moreover, it was thoroughly searched the theoretical framework related to the theme.A systematic search was conducted between December 15th and 25th 2014 via health-related databases: Pubmed, Medline, LILACS, SciELO and Cochrane Library, using combinations of the DeCS/MeSH terms ―ambient temperature‖, "health‖ and ―cardiovascular system‖ and their equivalent in Spanish and Portuguese, published between 2004 and 2014. A total of 47 publications were retrieved and 02 of which were excluded because they duplicate, 30 (66,7%) were excluded after title assessment and 06 (13,3%) after complete assessment of abstracts and the respective full texts. Thus, 09 papers (20,0%) met the inclusion criteria. Of the nine papers selected, 01 (11,1%) was published in 2009, 01 (11,1%) in 2010, 01 (11,1%) in 2012, 02 (22,2%) in 2011, and 04 (44,4%) in 2014. The Environmental Health Perspectives journal published two of the papers selected, while the others journals published one paper each: Gerontology, American Journal of Epidemiology, PLOS ONE, Medicine & Science in Sports & Exercise, Revista de Saúde Pública, Environmental Health, and Zhonghua Liu Xing Bing Xue Za Zhi. The papers found that changes in temperature are determinant in the process of physiological changes in the thermoregulatory system, predisposing mainly individuals with compromised adaptive capacity to the risk of cardiovascular lesions. Additionally, there was greater association between temperature and mortality due to metabolic, endocrine, and especially, cardiovascular causes. Two papers report that an increase of merely 1°C in daily maximum temperature increases mortality and urgent and emergency room visits due to cardiovascular diseases. Two papers (Associations between changes in city and address specific temperature and QT interval: The VA normative aging study e Brachial artery responses to ambient pollution, temperature, and humidity in people with type 2 diabetes: a repeated-measures study) related the increase in temperatures with greater vulnerability, mortality and morbidity in patients with Diabetes mellitus. Among the nine papers included, four papers described association between climatic changes and negative effects on health of elderly. Papers from different countries report that changes in ambient temperature alter the profile of hospitalizations, with an increased incidence of cardiovascular disorders, particularly in individuals with predisposing factors or comorbidities, such as being elderly and having Type 2 diabetes. The conclusion is that extreme ambient temperatures (very hot or very cold) are leading to increased incidence of cardiovascular diseases, especially in vulnerable populations.